Sociometric Status of Social Work Student in Malaysia - Lukman@Zawawi, Mohamad; Normala, Riza; Azlini, Chik (2018)
The study conducted following explanatory study with the intent to discover the facilitative and restrictive factors of undergraduate social work student involvement in social work student organizations. Social work student organizations can provide supplemental experiences for students for further shapeunderstanding and implementation of the social work profession’s core values. The total samples are 157 social work students from University Sultan Zainal Abidin (UniSZA). Factor Analysis (FA) has been applied in this study by using XLSTAT for further analysis. In FA, there are 4 most suitable variablesthat is >0.8 for factor analysis. The analyzing data of Correlation Matrix (r) was applied to know the relationship between membership status of PMKS and factor involvement in PMKS. After correlation matrix, Descriptive Statistic was performedto summarize the data such as mean by using simple statistics or charts. The method in this study can help the current social work student involvement in PMKS.